Um estudo observacional de rajadas de vento geradas por tempestades severas no Sul do Brasil - Ferreira, Vanessa (2017)
This study presents a climatology of convectively-generated strong wind gusts (SWG) occurred in Southern Brazil in the 2005-2015 period. The selection of these events was based on surface hourly data from the operational network of automated weather stations (AWSs) operated by Brazil’s National Meteorological Institute (INMET, in portuguese) and geostacionary meteorological satellite imagery. The time series of the atmospheric variables recorded by the AWSs during the SWGs events were evaluated aiming at detecting cold pools and mesohighs. Proximity soundings and Climate Forecast System Reanalysis (CFSR) and Climate Forecast System Version 2 (CFSv2) reanalysis data were used to assess the atmospheric environment during the occurence of the wind gust events. It was evalueted whether the atmospheric conditions highlight environments that discriminates the occurence of the SWG of those less intense. Moreover, a comparision was conducted among atmospheric profiles generated from CFSR/CFSv2 reanalysis and profiles obtained from operational soundings taken in Southern Brazil in the 1996-2015 period. The results showed that INMET’s AWS were able to sample convectively-driven cold pools and mesohighs following the wind gusts. The highest frequency of SWGs was in the spring and summer months. Most SWGs were detected from mid-afternoon to overnight hours. The western portion of Southern Brazil displayed the largest frequency of SWGs. The median value of pressure variations following the SWG +4,6 hPa, with extreme values (95% percentile) reaching +8,2 hPa. The median value for temperature variations was -6,5 C, with extremes values below -13,0 C. Overall, the results showed that the atmospheric parameters demonstrate some discrimination between SWGs and weaker wind gusts. The Downdraft Convective Available Potential Energy (DCAPE) and the Derecho Composite Parameter (DCP) were the atmospheric parameters that better discriminate the atmospheric environment favorable to the occurence of SWGs. The comparision between atmospheric profiles generated from CFSR/CFSv2 data and observed soundings showed that the reanalysis reproduce well the thermodynamic parameters, but significantly underestimates the kinematic parameters.